Minimization of the Copper Losses in Electrical Vehicle Using Doubly Fed Induction Motor Vector Controlled - S. Drid (ELECTRIC VEHICLES /Book2., 2011)
In this book, modeling and simulation of electric vehicles and their components have been emphasized chapter by chapter with valuable contribution of many researchers who work on both technical and regulatory sides of the field. Mathematical models for electrical vehicles and their components were introduced and merged together to make this book a guide for industry, academia and policy makers.